(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In the article on the material of speeches of the political leader of the country are considered particularly humanitarian discourse. Linguistic identity of the leader of the nation in its humanitarian discourse to some new approaches in our culture, discursive thinking, allowing at the same time to think about being a man of his spiritual and social culture. The authors propose to consider the humanitarian discourse as a result of the interaction of personal (student-centered) and institutional discourses. The object of study of this article is a metaphorical usage, representing the basic concepts of humanitarian discourse leader of the nation. This article discusses the function of metaphorical concepts of humanitarian discourse leader of the country as a means of influence and persuasion in the process of communicating with the global target (people). Conceptual metaphor representing the basic concepts of humanitarian discourse, is one of the most important means of categorization, conceptualization and evaluation of reality, reveals the essential features of political consciousness.